Sustentação por película comprimida de gás entre placas em movimento normal relativo - Salaverry, Ney Armando (1975)
A squeeze bearing experimental device was developed in order to investigate the squeeze film effects. A description is made of the developed components and the necessary instruments for control and measurements. Operation parameters were varied and the effects of suported mass motion and load capacity were analysed.